2010
DOI: 10.1007/s10659-010-9256-7
|View full text |Cite
|
Sign up to set email alerts
|

A Hamiltonian State Space Approach for 3D Analysis of Circular Cantilevers

Abstract: A 3D exact analysis of extension, torsion and bending of a cantilever of a circular cross section is studied with emphasis on the fixed-end effect. Through Hamiltonian variational formulation, the basic equations of elasticity in cylindrical coordinates and the boundary conditions of the problem are formulated into the state space setting in which the state vector comprises the displacement vector and the conjugate stress vector as the dual variables. Upon delineating the Hamiltonian characteristics of the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…The first and the second eigenvalues are zero and ±i are repeated eigenvalues. The non-zero eigenvalues may be used to estimate the stress disturbance due to the end conditions [7,8]. As the dimension b/a decreases, the eigenvalues for both orthotropic materials and isotropic materials increase, which implies the end effects diminish more rapidly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first and the second eigenvalues are zero and ±i are repeated eigenvalues. The non-zero eigenvalues may be used to estimate the stress disturbance due to the end conditions [7,8]. As the dimension b/a decreases, the eigenvalues for both orthotropic materials and isotropic materials increase, which implies the end effects diminish more rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Following the same line as the derivation for problems of circular cylinders [7,8], it can be shown that the symplectic orthogonality for the problem are …”
Section: Hamiltonian Properties Of the Eigensystemmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, the state matrix of the Hamiltonian state equations was symplectic and its eigenvalues have physical meaning. By expansion of the eigen-functions of the state matrix, Ding et al [40] and Tarn and co-workers [41][42][43][44][45] found some new solutions which were difficult or even impossible to be obtained by the original state space method. On the other hand, the state space equations in Hamiltonian system had the corresponding variational principle and it was convenient to develop approximate method, for example, finite element method, to solve the state equation [46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%